A Functional Size Measurement Procedure for MVC Applications from Source Code: Design, Automation and Empirical Evaluation - Quesada López, Christian Ulises (2014)
Software size has proved to be one of the main effort-and-cost drivers. It is widely accepted that software size is one of the key factors that has the potential to affect the effort and cost of the software projects. Functional size methods are hardly automatable and generally require a lengthy and costly process. FSM methods define generic concepts and measurement rules. The setup of a measurement procedure for each input to the measurement process is hence needed. A measurement procedure is defined as a set of operations described explicitly in order to measure according to a specific measurement method. A size estimation procedure based on the use of software development productivity models allows the management of development costs. Although accurate size estimation and effort prediction are very important for the success of any project, many practitioners have experienced difficulties in applying them. Thus, automated and simplified FSM methods are required. This research aims to proposing a functional size measuring procedure for Model-View-Controller (MVC) applications from source code. The research project includes the design, automation and empirical validation of a functional size measuring procedure, according to the ISO/IEC 20926 FPA CPM method. This proposal describes the research agenda of the PhD project. Research objective, background, relevant, prior work, research methods, threats to validity, current status and future plans are described in details. Since this is an ongoing work, this proposal looks for feedback from the expert community in order to improve its consistency as well as the reliability of the empirical validation.